Sedimentological evidences for subaerial exposure in the upper surface of Qamchuqa Formation, Bekhme area, northern Iraq - Rafee I. Al-Ehmeedy (Tikrit Journal of Pure Science, 2023)
The study deals with the upper contact of Qamchuqa Formation with the overlying Bekhme area of northern Iraq. This surface is characterized by presence of autobreccia bed including angular grains of (0.05_30cm in size) and composed of dolomite with disseminated black dolomite fragments which may indicates their subaerial exposure.